Russia, China, and the West : a contemporary chronicle, 1953 - 1966 - Deutscher, Isaac, 1907-1967 1907-1967 (Penguin Books, 1970)
"A history of the Soviet Union and its role in the world from the death of Stalin to Khrushchev's fall and the cultural revolution - built from articles written by one of the greatest observers of Soviet affairs" - p. 1 cover.